The Role of Riyadhah Habituation in Shaping the Character of Santri Spiritual Awareness - Siti Nurjanah; Ridwan Fauzi; Samsiah Samsiah (Penerbit Presisi Pustaka, 2025)
This study aims to analyze the role of riyadhah habituation in shaping the spiritual awareness and character of students at Pesantren Yasina Cigombong, Bogor. Riyadhah practices such as dzikir (remembrance), voluntary prayers, Qur’anic recitation, and fasting are regarded as spiritual exercises that function not only as routine worship but also as a method of character development. This research employed a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and documentation involving the pesantren’s caregivers, teachers (asatidz), and students. Data were analyzed through processes of reduction, presentation, and conclusion drawing, while data validity was ensured using source and method triangulation. The results indicate that riyadhah plays a significant role in cultivating discipline, responsibility, and sincerity in students’ spiritual practices. However, challenges remain, including low internal motivation, a sense of compulsion, and negative external influences. Supporting factors include teachers’ exemplary behavior, the pesantren’s religious culture, and family support. Therefore, riyadhah is proven to be an effective means of holistic spiritual character formation among students